PROBLEMS IN THE HEALTHCARE SYSTEM IN TURKESTAN AT THE END OF THE 19TH AND EARLY 20TH CENTURIES - Abdurahmonov Shohruh (Western European Studies, 2024)
This article examines the state of the healthcare system in Turkestan during the late 19th and early 20th centuries, a period marked by the region's colonization under the Russian Empire. It highlights the significant contributions of the Jadid reformers, who advocated for modernizing various societal sectors, including healthcare. The study explores the emergence of modern medical institutions and the efforts to incorporate advanced medical practices despite the challenges posed by religious conservatism and colonial neglect. Key figures such as Abu Ali ibn Sina and Sayid Islamkhoja are discussed, along with the impact of their work on the local population's health. The article also addresses the influence of foreign medical discoveries and the role of enlightened reformers in improving public health
Keywords: Turkestan healthcare system; 19th and 20th centuries; Russian Empire colonization; Jadid reformers